Single priming and a booster dose of 10-valent and 13-valent pneumococcal conjugate vaccine (PCV) maintains suppression of vaccine serotype colonization in South African children at 3, 4, and 5 years of age: a single-centre, open-labelled, randomized trial - Courtney P. Olwagen; Alane Izu; Lara Van der Merwe; Lisa Jose; Anthonet Koen; Shabir A. Madhi (Taylor & Francis Group, 2024)
Background Surveillance on nasopharyngeal Streptococcus pneumoniae carriage in older children would be informative in determining whether a single priming and booster dose of pneumococcal conjugate vaccine (PCV) provides durable protection against pneumococcal disease compared with traditional dosing schedules.Methods and objectives We report on the secondary study objective to evaluate overall, vaccine-serotype (VT), and non-vaccine serotype (NVT) S. pneumoniae colonization at 3, 4, and 5 years of age in children who were randomized to receive 10-valent or 13-valent PCV formulations at 6 (6w + 1) or 14 (14w + 1) weeks compared with a two-dose primary series (2 + 1), with all children receiving a booster dose at 9 months of age, using a multiplex nanofluidic qPCR assay.Results The prevalence of overall, VT, or NVT at 5 years of age between the 2 + 1 compared with the 6w + 1 or 14w + 1 groups for both PCV10 and PCV13 did not differ.Conclusion Although inconclusive, our findings suggest that a reduced 1 + 1 PCV dosing schedule is unlikely to increase breakthrough cases of VT pneumococcal disease in older children, which can inform decision-making on transitioning to a 1 + 1 schedule in South Africa.Clinical trial registration: The trial is registered at www.clinicaltrials.gov (identifier is NCT04275284).